Food Policy as a Wicked Problem: Contending with Multiple Demands and Actors. Issue 1 (1st March 2014) - Peters, B. Guy; Pierre, Jon
Abstract : Solving any policy problem is difficult but some are more difficult than are others. As food becomes a more central political issue the underlying conflicts between actors‐producers and consumers, GMO producers and opponents, etc.‐become more apparent and more intensely politicized. Further, food policy becomes more difficult to discuss independently and becomes embedded in other policy debates such as those over water, population and climate change. This paper conceptualizes food policy as a "wicked problem" and discusses how this concept originally derived from the planning literature illuminates the difficulties involved in making contemporary food policy.